Chromosome‐level genome of Pedinomonas minor (Chlorophyta) unveils adaptations to abiotic stress in a rapidly fluctuating environment. Issue 4 (8th June 2022) - Xu, Yan; Wang, Hongli; Sahu, Sunil Kumar; Li, Linzhou; Liang, Hongping; Günther, Gerd; Wong, Gane Ka‐Shu; Melkonian, Barbara; Melkonian, Michael; Liu, Huan; Wang, Sibo
Summary: The Pedinophyceae (Viridiplantae) comprise a class of small uniflagellate algae with a pivotal position in the phylogeny of the Chlorophyta as the sister group of the 'core chlorophytes'. We present a chromosome‐level genome assembly of the freshwater type species of the class, Pedinomonas minor . We sequenced the genome using Pacbio, Illumina and Hi‐C technologies, performed comparative analyses of genome and gene family evolution, and analyzed the transcriptome under various abiotic stresses. Although the genome is relatively small (55 Mb), it shares many traits with core chlorophytes including number of introns and protein‐coding genes, messenger RNA (mRNA) lengths, and abundance of transposable elements. Pedinomonas minor is only bounded by the plasma membrane, thriving in temporary habitats that frequently dry out. Gene family innovations and expansions and transcriptomic responses to abiotic stresses have shed light on adaptations of P. minor to its fluctuating environment. Horizontal gene transfers from bacteria and fungi have possibly contributed to the evolution of some of these traits. We identified a putative endogenization site of a nucleocytoplasmic large DNA virus and hypothesized that endogenous viral elements donated foreign genes to the host genome, their spread enhanced by transposable elements, located at gene boundaries in several of the expanded gene families.